Marketing research intended to deepen the degree of consumer perception regarding the consumption of dairy products - Violeta GAGU (LEOCĂ); Constanța Laura ZUGRAVU; Gheorghe Adrian ZUGRAVU (ACROSS)
This marketing research aimed to deepen the level of consumer perception regarding the consumption of dairy products, using the CAWI (Computer Assisted Web Interview) method. The study was conducted online, targeting a representative sample of consumers, and aimed to identify the main factors influencing consumption behaviour, such as taste preferences, health concerns, brand loyalty and environmental considerations. The research results indicate that taste and health benefits remain determining factors in the decision to purchase dairy products. At the same time, respondents showed an increased interest in products labelled as natural and ecological, reflecting a growing concern for sustainability. The CAWI method has proven effective in capturing a wide range of opinions, providing a clear picture of consumer preferences and attitudes.